2020
DOI: 10.1177/2066220320976112
|View full text |Cite
|
Sign up to set email alerts
|

Understanding offender managers’ views and experiences of psychological consultations

Abstract: Few studies have investigated the effectiveness of the psychological consultation process specifically for offender managers. This study involves a total of 23 offender managers’ views and perceptions of the consultation process within four areas of the North West of England. Within each location, a focus group was conducted involving between four and eight participants and interpretative phenomenological analysis was used to analyse the responses. The analysis revealed four main themes: validation of thoughts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Helpful elements reported by SWs included: the value of independent expertise; the formulation of a shared understanding amongst professionals; and the utility of having a safe space to discuss concerns. The findings regarding a safe space and independent expertise are echoed in Blinkhorn et al (2020) by offender managers. Similar themes around the concept of a safe space were also iterated by Evans et al (2011) in a residential care setting, highlighting the importance of consultees feeling safe during the consultation in order to develop their practice.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Helpful elements reported by SWs included: the value of independent expertise; the formulation of a shared understanding amongst professionals; and the utility of having a safe space to discuss concerns. The findings regarding a safe space and independent expertise are echoed in Blinkhorn et al (2020) by offender managers. Similar themes around the concept of a safe space were also iterated by Evans et al (2011) in a residential care setting, highlighting the importance of consultees feeling safe during the consultation in order to develop their practice.…”
Section: Discussionmentioning
confidence: 98%
“…The complexity of the consultant-consultee dynamic may therefore limit what the consultee is willing to share, as well as increasing the weight that is put on the consultant. It may be the case that the aforementioned ‘safe space’ may help to alleviate some of these feelings around the consultee feeling judged, as evidence indicates this allows the consultant to feel open about their practice and personal experiences around a case (Blinkhorn et al, 2020; Dimaro et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PICS formulates personality disorder from a trauma and attachment framework, and the main aims are to facilitate PPs' identification of the needs and risk of the PoP; to identify appropriate pathways; to up-skill the workforce via teaching and training; and to promote the psychological wellbeing of PPs and PoP. A recent study by Author (2021b) found that PPs particularly valued the emotional support offered by the PICS.…”
Section: Introductionmentioning
confidence: 99%